PENERAPAN MOTIF TENUN PANDAI SIKEK SEBAGAI ELEMEN ESTETIS PRODUK HOUSEWARE MELALUI ALAT TENUN BUKAN MESIN (ATBM) - Nalas Wasri, Dra. Minarsih, M.Sn., Drs. Erwin A, M.Sn. (Serupa The Journal of Art Education, 2017)
The aim of this final creation is to create the design of weafing which used weaving tool, not the machine on houseware product. The result of creation that achieved with the tittle pretty sweet, trophies, crown, cukia kaluak, star, ragi gadang jasmine, and palo fruit. The tittle taken from the design of Pandai Sikek that was simulation from weaving cloth. The final creation is made through five stages indudes the preparation’s stage (exploration), the stage of determination’s ideas (elaboration), synthesis, and the stage of settlement. This work made from manner manual, to produce the unique creation and having art value that used to beautivy the room.